INADEQUATE SUPPLY OF ELECTRICITY IN TECHNICAL COLLEGE WORKSHOPS IN DELTA STATE OF NIGERIA: PROBLEMS AND STRATEGIES FOR IMPROVEMENT - IFEYINWA (DR.), MKPUGHE CHRISTIANA; FIDELIS, ENUMA (IJRDO- Journal of Educational Research, 2017)
Electricity which is the flow of current through wires of a conductor in the circuit is of vitalimportance to man and the country. The use of electricity in the technical colleges cannot beoveremphasized. This work focuses on inadequate supply of electricity in Technical Collegeworkshops, some important terms used in electricity transmission, types of workshops, uses ofelectricity, problems associated with the use of electricity, such as illegal connection, lack offinance, lack of competent manpower, vandalization of electricity components or accessories,lack of security. This study came up so that these lapses can be corrected, so that there will bemaximum utilization of electricity in the technical college workshops. Strategies forimprovement were recommended based on the findings which include government should sendenough allocations to schools for the running and management of technical colleges;government should pay the electricity bills of technical colleges in the Delta State and schoolswithout electricity should be electrified, practical teachers should supervise their studentsduring electrical installation classes and ensure that all wiring are properly tested beforeapproval and so on.